A framework of scalable optical metropolitan networks for improving survivability and class of service. - Pin-Han Ho (IEEE Network : the magazine of global information exchange)
The issues of scalability and class of service have been among the most important research focuses in design of the control plane for wavelength-routed WDM networks. We introduce a framework for achieving a scalable design in metropolitan area networks with WDM as the core technology (called optical metropolitan networks). The framework is summarized with the topics of survivability, scalability and class of service. A novel design concept, called interarrival planning, which aims to achieve scalable control and management in optical metropolitan networks, is addressed